PENGARUH STRUKTUR KEPEMILIKAN TERHADAP RISK MANAGEMENT DISCLOSURE (Studi pada perusahaan perbankan yang terdaftar di Bursa Efek Indonesia 2013- 2015) - Mochammad Taufik Taufani; Noor Shodiq Askandar; Abdul Wahid Mahsuni (Universitas Islam Malang, 2017)
Abstraksi The purpose of this research is 1) to know the influence of manajerial ownership toward risk management disclosure, 2) to know the effect of institutional ownership to risk management disclosure, 3) to know the influence of foreign ownership to risk management disclosure, 4) to know the effect of public ownership to risk management disclosure. The population used in this study are all banking companies listed on the Indonesia Stock Exchange (BEI) in 2013-2015. Sample selection using purposive sampling. Based on the criteria, obtained 43 companies that became the sample in this study. The method used in this study using multiple linear regression method. Based on the results of the analysis can be put forward several conclusions as follows: 1) T test results show that for manajerial ownership variable has significant effect on risk management disclosure, but institutional domestic ownership, foreign ownership, and public ownership has no significant effect on risk management disclosure. 2) The result of f test shows that manajerial ownership, institutional domestic ownership, foreign ownership, public ownership simultaneously have significant influence to risk management disclosure. Keywords: Ownership Structure, Risk Management Disclosure.